ANALISIS PELANGGARAN HAK CIPTA OLEH MALL GRAND INDONESIA YANG MENGGUNAKAN SKETSA TUGU SELAMAT DATANG SEBAGAI LOGO MALL BERDASARKAN PASAL 1 UU NO. 28 TAHUN 2014 TENTANG HAK CIPTA - Shilvia Rahayu Safitri (JOURNAL OF LAW AND NATION, 2024)
Case of copyright infringement committed by PT. Grand Indonesia regarding the copyright of the sketch of the welcome monument owned by the late. Henk Ngantung. The late Henk Ngantung made a sketch of a monument to a pair of men and women waving their hands in 1962. The sketch was made in the form of a statue located at the Hotel Indonesia (HI) roundabout which was named the Welcome statue. This creation has been recorded at the Ministry of Law and Human Rights of the Republic of Indonesia, Directorate General of Intellectual Property with Copyright Certificate No. 46190 so as to obtain protection rights for the creator during his or her lifetime and for the copyright holder after the creator dies within the time period determined by the Copyright Law. And it has been recorded and published with No. HKI.2-KI.01.01-193 dated 25 October 2019 with copyright transfer recorded no. 46190, namely the art of sketching the Welcome Monument which is currently recorded under the names of its heirs.